Analisis Kebutuhan Pengembangan Media Video Interaktif Berbasis Budaya Lokal Gayo ‘Didong’ untuk Meningkatkan Literasi Budaya dan Kewargaan Siswa Sekolah Dasar - Nur Hafidhah; Rapita Aprilia; Inge Ayudia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify the needs for developing interactive video-based learning media rooted in the local Gayo culture, specifically the traditional "Didong" dance, to enhance cultural literacy and civic understanding among elementary school students. A descriptive qualitative approach was employed, with the researcher serving as the primary instrument for data collection and analysis. Data were gathered through observations and interviews. The findings reveal that students exhibit low motivation in cultural learning, largely due to the monotonous nature of the instructional media currently in use. This underscores the need for innovative and engaging teaching media. In response, the study proposes the development of interactive video learning media that incorporates dynamic visual elements, with the aim of increasing student engagement and supporting the learning objectives of cultural arts and civics education, particularly in promoting the appreciation and preservation of the traditional "Didong" dance.